Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper, 2008)
This paper provides a semi-annual review of the status of financing for PRGFESF lending, HIPC and MDRI debt relief, and an update on the mobilization of resources for the subsidization of emergency assistance to PRGF-eligible countries. The last review was completed by the Executive Board on September 26, 2007.